2018
DOI: 10.1038/s41598-018-20565-0
|View full text |Cite
|
Sign up to set email alerts
|

TDP-43 self-interaction is modulated by redox-active compounds Auranofin, Chelerythrine and Riluzole

Abstract: Amyotrophic lateral sclerosis (ALS) represents a fatal neurodegenerative disease, which is characterized by a rapid loss of lower and upper motor neurons. As a major neuropathological hallmark, protein aggregates containing the Transactivating Response Region (TAR) DNA Binding Protein (TDP-43) are detectable in about 95% of sporadic ALS patients. TDP-43 interacts with itself physiologically to form liquid droplets, which may progress to pathological aggregates. In this study, we established the NanoBit lucifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…In summary, riluzole inhibits the catalytic activity of CK1δ, decreases TDP‐43 hyperphosphorylation, and consequently TDP‐43 aggregation and cytoplasmic mislocalization, one of the principal pathological hallmarks of ALS. As reported by an independent screening of known active molecules from the LOPAC® library, riluzole was already classified as TDP‐43 self‐interaction inhibitor, with an unknown mechanism of action . Curiously, the same work found that the concentration at which riluzole exerts its maximum effect is around 10 μ m , in agreement with the IC 50 value determined in vitro toward CK1δ.…”
Section: Figuresupporting
confidence: 71%
See 1 more Smart Citation
“…In summary, riluzole inhibits the catalytic activity of CK1δ, decreases TDP‐43 hyperphosphorylation, and consequently TDP‐43 aggregation and cytoplasmic mislocalization, one of the principal pathological hallmarks of ALS. As reported by an independent screening of known active molecules from the LOPAC® library, riluzole was already classified as TDP‐43 self‐interaction inhibitor, with an unknown mechanism of action . Curiously, the same work found that the concentration at which riluzole exerts its maximum effect is around 10 μ m , in agreement with the IC 50 value determined in vitro toward CK1δ.…”
Section: Figuresupporting
confidence: 71%
“…Lou Gehrig's disease, also known as amyotrophic lateral sclerosis (ALS) or motor neuron disease (MND), is a progressive and fatal neurodegenerative disorder that involves both upper and lower motor neurons in the brain and spinal cord . Clinical symptoms reported in affected patients range from muscles weakening to spasticity, resulting in difficulty in movements, poor functional capacity and, in the final stages of the disease, respiratory failure . Prognosis is grim, life expectancy rarely exceeds five years, and available drugs only mitigate progression of the illness .…”
Section: Figurementioning
confidence: 99%
“…Our study is the first to indicate that riluzole administration does not alter total levels of TDP-43, nor does riluzole affect accumulation of insoluble and phosphorylated TDP-43. Recent studies have suggested that riluzole may exert its actions through a direct link on TDP-43 self-interaction, without change to total TDP-43 levels in neuroblastoma cells in vitro (30). Furthermore, it has been hypothesised that expression of a truncated protein kinase, CK1δ, leads to phosphorylation, mislocalisation and aggregation of TDP-43 (31), and that riluzole is may inhibit this process (10).…”
Section: Discussionmentioning
confidence: 99%
“…In ALS-mouse models, non-functional proteins secondary to the oxidation of amino acid residues by peroxynitrite have been observed (Yoshino and Kimura, 2006). In addition, oxidative damage results in the aggregation of TDP-43, the major disease-associated protein involved in the pathogenesis of ALS (Moujalled et al, 2017;Oberstad et al, 2018) that promotes OS in neuronal cells (Duan et al, 2010;Cohen et al, 2012Cohen et al, , 2015Magrané et al, 2014) (Figure 1).…”
Section: High Levels Of Certain Types Of Ros (H 2 O 2 and O •−mentioning
confidence: 99%